Currículo de matemática na Educação Infantil de um município do interior paulista: compreensão de número e sistema de numeração - Torres, Valmir Rogério (Universidade Federal de São Carlos, 2023)
This research presents an analysis of the Curriculum of the Municipal Education Network of Limeira, more specifically the part related to early childhood education. Its purpose is to verify how the contents related to mathematics, numbers and the numbering system are presented in this teaching stage. For this purpose, the conceptions of teaching-learning, student, teacher, curriculum itself and its characteristics were initially analyzed. The analyzes were carried out based on legal documents and Census data, aiming to demonstrate the evolution of early childhood education and its importance for the educational process and for the progress of society. Regarding the functionality of the teaching-learning process, progressive and liberating theories were used, which focus on the development of critical and participatory citizens, relating learning to their social context, based on the theories of Vygotsky, Rogoff and Paulo Freire. In the same way, a vision of curriculum was adopted that does not have the purpose of serving as social control, adopting Apple's propositions. With regard to mathematics, a historical view was adopted and the use of multiple intelligences with contributions from the theories of Smole, Boyer and Mezscach. In methodological terms, scientific research was used to support this work, based on document analysis and Bardin's content analysis technique, which allowed selecting points in the analyzed document that could be discussed to achieve the research objectives. Among the results presented, there was a lack of scientific research on the knowledge of newborn babies and the need to propose educational actions that consider the child's reality and social context.
Mathematics curriculum in early childhood education in a city in the interior of São Paulo: understanding numbers and the numbering system
Keywords: Desenvolvimento e aprendizagem; Teoria curricular e linguagem; Matemática; Development and learning; Curriculum theory and language; Mathematics; CIENCIAS HUMANAS::EDUCACAO::CURRICULO